On Itô's formula for multidimensional Brownian motion - Hans Föllmer; Philip E. Protter (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
Consider a d-dimensional Brownian motion X (Xl, ... ,Xd ) and a function F which belongs locally to the Sobolev space W 1,2. We prove an extension of Ito's formula where the usual second order terms are replaced by the quadratic covariations [fk(X), Xkj involving the weak first partial derivatives fk of F. In particular we show that for any locally square-integrable function f the quadratic covariations [f(X), Xkj exist as limits in probability for any starting point, except for some polar set. The proof is based on new approximation results for forward and backward stochastic integrals.
urn:nbn:de:kobv:11-10051072
Keywords: 330; Ito's formula; Brownian motion; stochastic integrals; quadratic covariation; Dirichlet spaces; polar sets